Crop photoperiodism model 2.0 for the flowering time of sorghum and rice that includes daily changes in sunrise and sunset times and temperature acclimation - Clerget, B.; Sidibe, M.; Bueno, C.S.; Grenier, C.; Kawakata, T.; Domingo, A.J.; Layaoen, H.L.; Gutiérrez-Palacios, N.D.; Bernal, J.H.; Trouche, G.; Chantereau, J. (Oxford University Press, 2021)
Daylength determines flowering dates. However, questions remain regarding flowering dates in the natural environment, such as the synchronous flowering of plants sown simultaneously at highly contrasting latitudes. The daily change in sunrise and sunset times is the cue for the flowering of trees and for the synchronization of moulting in birds at the equator. Sunrise and sunset also synchronize the cell circadian clock, which is involved in the regulation of flowering. The goal of this study was to update the photoperiodism model with knowledge acquired since its conception.A large dataset was gathered, including four 2-year series of monthly sowings of 28 sorghum varieties in Mali and two 1-year series of monthly sowings of eight rice varieties in the Philippines to compare with previously published monthly sowings in Japan and Malaysia, and data from sorghum breeders in France, Nicaragua and Colombia. An additive linear model of the duration in days to panicle initiation (PI) and flowering time using daylength and daily changes in sunrise and sunset times was implemented.Simultaneous with the phyllochron, the duration to PI of field crops acclimated to the mean temperature at seedling emergence within the usual range of mean cropping temperatures. A unique additive linear model combining daylength and daily changes in sunrise and sunset hours was accurately fitted for any type of response in the duration to PI to the sowing date without any temperature input. Once calibrated on a complete and an incomplete monthly sowing series at two tropical latitudes, the model accurately predicted the duration to PI of the concerned varieties from the equatorial to the temperate zone.Including the daily changes in sunrise and sunset times in the updated photoperiodism model largely improved its accuracy at the latitude of each experiment. More research is needed to ascertain its multi-latitudinal accuracy, especially at latitudes close to the equator.